O gênero comentário online: interação dialógica e polêmica na rede social Instagram - PEREIRA, Maiara Amorim (2024)
This research deals with a study of the online commentary genre, aiming to investigate the dialogical-evaluative and controversial relationships that act in the construction of the genre's meanings. Online commentary is made up of a multiplicity of dialogic threads and, in the journalistic sphere, it materializes controversy, aspects that make us consider its analysis relevant. The research is guided by the dialogic theory of the Prague Linguistic Circle and theories from the field of discourse, we establish dialogues mainly with authors such as: Volóshinov (2018), Bakhtin (2013, 2015), Amossy (2017, 2020), Authier-Revuz (2004), Paveau (2021), among others. From a methodological point of view, the research is basic in nature, descriptive and documentary in nature. The corpus consists of 38 online comments from the political-journalistic sphere. The description of the data was made based on the analysis of online comments, collected in news published on two profiles on the social network Instagram, namely: Carta Capital and CNN Brasil. The news (source text) deals with two specific themes: the demonstrations on January 8, 2023 and Nicolás Maduro's visit to Brazil. The research is based on the following concerns: how is the construction of dialogic-evaluative relationships in the online commentary genre about news? How do linguistic elements, the extraverbal context, and the evaluative and ideological aspects act in this construction of meanings? How do interactions sustain controversy in this genre? At the end of the analyses, it was possible to observe that the online comment genre is conducive to the materialization of dialogical relationships. Internet users dialogue with each other, establishing connections both with the content of the news and with other external discursive threads, mobilized to help expand discussions in the comments. These aspects point to the presence of interlocutive and interdiscursive dialogism. The recurrent dialogical relationships in online commentary are those without linguistic marks delimiting boundaries between one discourse and another, with this, it was possible to observe the occurrence of heterogeneity shown unmarked, given the presence of resources such as: irony, allusion and discourse indirect. It was observed that, regardless of the portals, the comments present speeches marked by dissent, with disagreement prevailing, which favored the construction of a controversial argument, with the occurrence of comments that express arguments such as: the distortion of the point of view, the argumentum ad hominem, disqualification, dichotomization, polarization, among others. Furthermore, there is mention of political figures in the comments, which suggests the incidence of ideological threads in the discussions.